Nicotinamide riboside supplementation restores microglial health and improves cognition in aged male mice - Ramkumar Thiyagarajan; Rupadevi Muthaiah; Bhavana Sreevelu; Owen P. Treanor; Yonas Redae; Reem Berman; Anna L. Davis; Nanda Yellapu; Spencer R. Rosario; Lee D. Chaves; Kenneth L. Seldeen; Bruce R. Troen (GeroScience, 2025)
Cognitive impairment affects 1 in 6 individuals over 60, with over 75 million projected by 2030. Age-related changes in microglial function and declining nicotinamide adenine dinucleotide (NAD + ) levels may contribute to cognitive decline. Although nicotinamide riboside (NR) supplementation can restore NAD + levels in aged mice, its effects on microglial phenotype and cognition during normal aging remain unclear. We assessed cognitive function, neuroinflammation, and microglial gene expression in 6-month (Young) and 22-month (Aged) mice, along with aged mice supplemented with NR (Aged + NR; 400 mg/kg body weight) for 8 weeks. Aged mice exhibited impaired cognition and increased gene expression related to neuroinflammation. NR supplementation improved or prevented the decline in nest-building ability, Y-maze spontaneous alternation, and novel object recognition, which are reflective of instrumental activities of daily living, spatial working memory, and recognition memory. NR supplementation diminished microglial (IBA1) and astrocytic (GFAP) activation, resembling the young phenotype. Gene expression profiling revealed reduced microglial activation, inflammatory pathways, and chemokine production in Aged + NR mice, along with upregulation of genes associated with learning, memory, and gliogenesis. NR lowered transcriptional signatures from age-dependent (ADEM) and disease-associated (DAM) microglia and enhanced homeostatic state profiles. Metabolic pathway analysis of microglial transcripts indicated that NR suppressed age-induced increases in fatty acid metabolism. This was supported by immunostaining, which showed reduced lipoprotein lipase (LPL), a DAM marker, in the cortex and hippocampus. Overall, NR appeared to mitigate age-related cognitive decline by shifting microglial gene expression and metabolism toward a younger phenotype, suggesting potential therapeutic relevance for healthy brain aging.

Ecological succession on 3D printed ceramic artificial reefs - Asa Oren; Ofer Berman; Reem Neri; Maaian Edery-Lutri; Natalie Chernihovsky; Ezri Tarazi; Nadav Shashar (Science of The Total Environment, 2024)

Three-Dimensional-Printed Coral-like Structures as a Habitat for Reef Fish - Asa Oren; Ofer Berman; Reem Neri; Ezri Tarazi; Haim Parnas; Offri Lotan; Majeed Zoabi; Noam Josef; Nadav Shashar (Journal of Marine Science and Engineering, 2023)
Coral reefs are three-dimensional biogenic structures that provide habitat for plenty of marine organisms; yet, coral reefs are deteriorating worldwide. Hence, it is essential to identify suitable substitutes for such coral services. This study examines reef fishes’ behavior and reactions to three-dimensional-printed (3DP) corals based on scanned Stylophora pistillata, as well as modified 3DP models. In particular, fishes’ unresponsiveness to the color, shape, morphology, and material of 3DP models both in vitro and in situ experiments was investigated. Coral reef fishes responded to the 3DP corals and demonstrated their usage in a range of services. Moreover, a greater number of fish species interacted more with 3DP models than they did with live corals. Furthermore, specific reef fish species, such as Sea Goldies (Pseudanthias squamipinnis), showed a preference for specific 3DP coral color, and other species demonstrated preferences for specific 3DP model shapes. The current study results show that three-dimensional-printed coral models can substitute for live corals for certain types of reef fish services.

Design and application of a novel 3D printing method for bio-inspired artificial reefs - Ofer Berman; Michael Weizman; Asa Oren; Reem Neri; Haim Parnas; Nadav Shashar; Ezri Tarazi (Ecological Engineering, 2023)